2015
DOI: 10.1038/ncomms7491
|View full text |Cite
|
Sign up to set email alerts
|

The solar magnetic activity band interaction and instabilities that shape quasi-periodic variability

Abstract: Solar magnetism displays a host of variational timescales of which the enigmatic 11-year sunspot cycle is most prominent. Recent work has demonstrated that the sunspot cycle can be explained in terms of the intra- and extra-hemispheric interaction between the overlapping activity bands of the 22-year magnetic polarity cycle. Those activity bands appear to be driven by the rotation of the Sun's deep interior. Here we deduce that activity band interaction can qualitatively explain the ‘Gnevyshev Gap'—a well-esta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
90
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(97 citation statements)
references
References 47 publications
(80 reference statements)
5
90
1
Order By: Relevance
“…Indeed, the degree and frequency dependence of the solar frequency shifts were observed to be different for the QBO and the 11-yr cycle. The larger frequency shifts of the QBO measured for the quadripolar l = 2 modes ) were explained to be associated with an equatorial and deeper concentration of the structural changes in the QBO, as also suggested by Ulrich & Tran (2013) and McIntosh et al (2015). Furthermore, KIC 10644253 is likely to have a very inclined rotation axis (see Table 1), although we cannot be more precise since the differences between the measurements exceed their reported uncertainties.…”
Section: Discussionmentioning
confidence: 45%
“…Indeed, the degree and frequency dependence of the solar frequency shifts were observed to be different for the QBO and the 11-yr cycle. The larger frequency shifts of the QBO measured for the quadripolar l = 2 modes ) were explained to be associated with an equatorial and deeper concentration of the structural changes in the QBO, as also suggested by Ulrich & Tran (2013) and McIntosh et al (2015). Furthermore, KIC 10644253 is likely to have a very inclined rotation axis (see Table 1), although we cannot be more precise since the differences between the measurements exceed their reported uncertainties.…”
Section: Discussionmentioning
confidence: 45%
“…Snodgrass (1983) finds this same latitude as a peak of differential rotation shearing. This latitude was further revealed as a zone of interest by McIntosh et al (2014McIntosh et al ( , 2015, who found a scarcity of EUV bright points above this latitude, as well as a distinct evolution pattern of the magnetic range of influence (MRoI) divided by this latitude. While the coronal hole polar boundary is determined by properties of the polar field itself, several other quantities show variation nearby.…”
Section: Latitude Coronal Hole Profilesmentioning
confidence: 99%
“…In this present study, we use the same technique and the same database, which is further extended to August 2014, however. The extended database covers a significant portion of the current Solar Cycle 24, and hence provides an opportunity to compare coronal hole properties between the past Cycle 23 and this special new cycle, which, after an unexpectedly deep minimum, slowly started around 2010, and rose to a low maximum in early 2014 (McIntosh et al, 2015). Lowder et al (2014) have also measured coronal hole areas, and the unsigned and signed total flux measured in these holes, distinguishing polar regions from low latitudes with an arbitrary division at ± 65 degrees.…”
mentioning
confidence: 99%
“…In addition, they tend to be ephemeral, being most obvious only during certain intervals of particular cycles, and with periods that may change with time. Maybe the particularly clear periodicities observed during Cycle 24 as discussed here, together with a convincing link with phenomena deep in the Sun, such as suggested by McIntosh et al (2015), will invigorate interest in this topic and lead to an improved understanding of these variations and their consequences throughout the heliosphere.…”
Section: Summary and Discussionmentioning
confidence: 58%
“…Recently, McIntosh et al (2015) have suggested that the variability in the number of flares, CMEs, particle events, and other solar and interplanetary phenomena is driven by surges of magnetism from activity bands of the 22-year solar cycle which are in turn driven by the deep solar interior. They characterize this variability as quasi-annual, and suggest that the Rieger-like periods are what they term "hybrid" periodicities that arise from quasi-annual periodicities that are out of phase in each solar hemisphere such that, depending on the phasing, the Rieger periods are more or less visible in a whole-Sun time series.…”
Section: Summary and Discussionmentioning
confidence: 99%